2002
DOI: 10.1021/ja0178012
|View full text |Cite
|
Sign up to set email alerts
|

Modified Phthalocyanines for Efficient Near-IR Sensitization of Nanostructured TiO2 Electrode

Abstract: A zinc phthalocyanine with tyrosine substituents (ZnPcTyr), modified for efficient far-red/near-IR performance in dye-sensitized nanostructured TiO(2) solar cells, and its reference, glycine-substituted zinc phthalocyanine (ZnPcGly), were synthesized and characterized. The compounds were studied spectroscopically, electrochemically, and photoelectrochemically. Incorporating tyrosine groups into phthalocyanine makes the dye ethanol-soluble and reduces surface aggregation as a result of steric effects. The perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
251
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(261 citation statements)
references
References 39 publications
6
251
1
2
Order By: Relevance
“…It is generally accepted that RhB molecules are sensitive to visible light and a dye-sensitized photodegradation path, instead of photocatalytic degradation, may possibly occur [49]. To exclude this possibility, 2,4-DCP, a colorless organic pollutant, was typically chosen to confirm the visible-light-driven photocatalytic destruction ability of sample 8%WTS0.7, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that RhB molecules are sensitive to visible light and a dye-sensitized photodegradation path, instead of photocatalytic degradation, may possibly occur [49]. To exclude this possibility, 2,4-DCP, a colorless organic pollutant, was typically chosen to confirm the visible-light-driven photocatalytic destruction ability of sample 8%WTS0.7, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 Song et al 4 showed that diarylamine chlorosilane (Ar 2 N-(CH 2 ) n -SiCl 3 , Ar = 3,4-difluorophenyl) redox-active modifiers can serve as a hole-selective interfacial layer on an ITO electrode in bulk-heterojunction OPVs; the PCE of these devices was slightly higher than that of devices in which PEDOT:PSS was utilized as the interfacial layer. 4 These and other papers [15][16][17][18][19][20][21] have demonstrated that the molecular design of a redox-active modifier, such as the type, position and length of its bridging moiety and the presence of solubilizing groups or bulky substituents, may significantly affect the charge-collection kinetics and efficiency at modified TCO surfaces, because these structural parameters dictate properties such as molecular orientation, tunneling distance, degree of aggregation, and/or interface dipole magnitude and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies and methods for modifying the optical properties of TiO 2 particles, e.g., doping of a transition metal [3,4], plasma treatments [5] and nitrogen doping [6,7], have been proposed, and photoactivity under visible-light irradiation has been proved in some limited reactions. Much interest has also been shown in surface modification of TiO 2 with transition metal complexes and/or organic dyes for construction of dye-sensitized photocatalytic systems that work under visible-light irradiation [8,9] as well as for improvement of the efficiency of dye-sensitized solar cells [10][11][12].…”
Section: Introductionmentioning
confidence: 99%